UJI PEMBERIAN PUPUK KANDANG BURUNG PUYUH TERHADAP HASIL PRODUKSI SAWI HIJAU (Brassica juncea L) - Latifatul Khulud (Universitas Islam Balitar, 2021)
The purpose of this study was to determine the effect of quail manure application on the production of mustard greens. This study was conducted using a Randomized Group Design (RAK) with 5 levels and 3 repeats, with a factor of quail manure (P) 0 tons / ha (P0), 5 tons / ha (P1), 10 tons / ha (P2), 15 tons / ha (P3), 20 tons / ha (P4), 25 tons / ha (P5). The results of research on the application of quail manure to the production of mustard greens (Brassica Juncea L) have a noticeable influence on changing the length, leaf circumference, plant length, plant weight and stem diameter. The application of manure manure for quail droppings of 20 tons/ha (P4) provides the highest variable for all growth and yield of mustard plants.